FORMAT OTONOMI DESA MENURUT UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - Ade Kosasih (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2016)
Political autonomy law of village is very varied because the arrangement of village in UUD 1945 is very briefly, featuring multiple interpretations, so that the organic regulations are always change appropriate with the taste of the rulers. By the amendment of UUD 1945, provisions on the village changed so that the village can adjust to the conditions of rural communities.  The presence of Law Number 6 of 2014 about village gives new expectation to reposition the village on the first position, although there is pessimistic associated local wisdom that has been destroyed. Based on that background raised issues such as the following : How is the position of the village in order  UUD 1945 and its amendment? How is format of village autonomy according to law Legal Number 6 of 2014? To answer these problems, doing research using normative method, which researching secondary data with the legal approach, then analyzed using analytical juridical method. Based on the results of research, rural arrangement in UUD 1945 after the amendment provides an opportunity to adjust to the conditions of each village. The presence of Legal Number 6 of 2014, gives a new format to the standing of village so the village is no longer be a sub-system of local government. However the village serves as an autonomous region based on the principles recognition and subsidiarity with the appropriate form of options provided by UUD NRI of 1945.  Keywords: Format, Autonomy, Village.